Potensi Kedelai sebagai Nutrisiuntuk Pencegahan Nefropati Diabetes pada Penderita Diabetes Melitus: Potential of Soybean as a Nutrient for the Prevention of Diabetic Nephropathy in Patients with Diabetes Mellitus - Putri Dafriani (Fakultas Keperawatan Universitas Andalas, 2015)
Diabetes mellitus is the fourth of five causes of death in developed countries . This trend extends to developing countries and newly industrialized countries . Diabetic nephropathy is one of the complications of diabetes are the leading cause of end stage renal disease . The purpose of this literature review is to discuss the influence of soy genistein in dealing with diabetic nephropathy . Genistein is one isoflavone soy has many benefits, especially in the prevention of diabetic nephropathy . Inflammation is one of the theories that underlie the occurrence of diabetic nephropathy . Genistein can inhibit the inflammatory process due to hyperglycemia . Soy can be used as a nutrient for diabetics that can prevent diabetic nephropathy .